Genome-wide interaction study of smoking behavior and non-small cell lung cancer risk in Caucasian population. (20th October 2017) - Li, Yafang; Xiao, Xiangjun; Han, Younghun; Gorlova, Olga; Qian, David; Leighl, Natasha; Johansen, Jakob S; Barnett, Matt; Chen, Chu; Goodman, Gary; Cox, Angela; Taylor, Fiona; et al.
Abstract : We conducted a genome-wide gene-smoking interaction analysis in non-small cell lung cancer using genotype from 35737 individuals including both discovery and validation datasets. We identified three novel SNPs with significant interactions with tobacco smoking. Abstract: Non-small cell lung cancer is the most common type of lung cancer. Both environmental and genetic risk factors contribute to lung carcinogenesis. We conducted a genome-wide interaction analysis between single nucleotide polymorphisms (SNPs) and smoking status (never- versus ever-smokers) in a European-descent population. We adopted a two-step analysis strategy in the discovery stage: we first conducted a case-only interaction analysis to assess the relationship between SNPs and smoking behavior using 13336 non-small cell lung cancer cases. Candidate SNPs with P -value <0.001 were further analyzed using a standard case–control interaction analysis including 13970 controls. The significant SNPs with P -value <3.5 × 10 −5 (correcting for multiple tests) from the case–control analysis in the discovery stage were further validated using an independent replication dataset comprising 5377 controls and 3054 non-small cell lung cancer cases. We further stratified the analysis by histological subtypes. Two novel SNPs, rs6441286 and rs17723637, were identified for overall lung cancer risk. The interaction odds ratio and meta-analysis P -value for these two SNPs were 1.24 with 6.96 × 10 −7 and 1.37 with 3.49 × 10 −7, respectively. In addition, interaction of smoking with rs4751674 was identified in squamous cell lung carcinoma with an odds ratio of 0.58 and P -value of 8.12 × 10 −7 . This study is by far the largest genome-wide SNP-smoking interaction analysis reported for lung cancer. The three identified novel SNPs provide potential candidate biomarkers for lung cancer risk screening and intervention. The results from our study reinforce that gene-smoking interactions play important roles in the etiology of lung cancer and account for part of the missing heritability of this disease.